Cryptochrome mediated magnetic sensitivity in Arabidopsis occurs independently of light-induced electron transfer to the flavin. Issue 3 (17th February 2020) - Hammad, M.; Albaqami, M.; Pooam, M.; Kernevez, E.; Witczak, J.; Ritz, T.; Martino, C.; Ahmad, M.
Abstract : Arabidopsis cryptochrome-dependent magnetosensitivity occurs via a reaction that does not require light. This excludes radical pairs formed during light-triggered electron transfer to the flavin. Abstract : Cryptochromes are highly conserved blue light-absorbing flavoproteins which function as photoreceptors during plant development and in the entrainment of the circadian clock in animals. They have been linked to perception of electromagnetic fields in many organisms including plants, flies, and humans. The mechanism of magnetic field perception by cryptochromes is suggested to occur by the so-called radical pair mechanism, whereby the electron spins of radical pairs formed in the course of cryptochrome activation can be manipulated by external magnetic fields. However, the identity of the magnetosensitive step and of the magnetically sensitive radical pairs remains a matter of debate. Here we investigate the effect of a static magnetic field of 500 μT (10× earth's magnetic field) which was applied in the course of a series of iterated 5 min blue light/10 min dark pulses. Under the identical pulsed light conditions, cryptochrome responses were enhanced by a magnetic field even when exposure was provided exclusively in the 10 min dark intervals. However, when the magnetic stimulus was given exclusively during the 5 min light interval, no magnetic sensitivity could be detected. This result eliminates the possibility that magnetic field sensitivity could occur during forward electron transfer to the flavin in the course of the cryptochrome photocycle. By contrast, radical pair formation during cryptochrome flavin reoxidation would occur independently of light, and continue for minutes after the cessation of illumination. Our results therefore provide evidence that a magnetically sensitive reaction is entwined with dark-state processes following the cryptochrome photoreduction step.